DARI PIAGAM MENJADI RELIK: Pergeseran Pemaknaan Prasasti yang tersimpan di dalam Pura-pura di Kawasan Danau Batur, Bali - Tjahjono Prasodjo (Balai Arkeologi Yogyakarta, 2011)
Villages around Lake Batur, Bangli District, Bali Province have many inscriptions kept in their puras. The inscriptions have been experiencing a transformation of significance which is very different from the original meaning and function of an inscription. This article is meant to reveal the process of transformation of the inscriptions kept in the temples in the vicinity of Lake Batur. Based on the results of field observations and literature studies have been known that there are ancient inscriptions kept in at least five temples in the villages around Lake Batur. The inscriptions contain a very significant historical and socio-cultural data about local history. However, historians and archaeologist are very difficult to access the data. There has been a change of how the community sees the significance of an inscription, shifting from a charter to a very sacred relic. Such changes must be addressed wisely by the researchers and the community as the owner and